The best fixation target revisited : New insights from retinal eye tracking - Niehorster, Diederick C ; 0000-0002-4672-8756; Tamborski, Szymon; Nyström, Marcus ; 0000-0002-2089-9012; Konklewski, Robert; Pryhodiuk, Valentyna; Tołpa, Krzysztof; Hessels, Roy S; Szkulmowski, Maciej; Hooge, Ignace T C (Behavior Research Methods, 2025)
In many tasks, participants are instructed to fixate a target. While maintaining fixation, the eyes nonetheless make small fixational eye movements, such as microsaccades and drift. Previous work has examined the effect of fixation point design on fixation stability and the amount and spatial extent of fixational eye movements. However, much of this work used video-based eye trackers, which have insufficient resolution and suffer from artefacts that make them unsuitable for this topic of study. Here, we therefore use a retinal eye tracker, which offers superior resolution and does not suffer from the same artifacts to reexamine what fixation point design minimizes fixational eye movements. Participants were shown five fixation targets in two target polarity conditions, while the overall spatial spread of their gaze position during fixation, as well as their microsaccades and fixational drift, were examined. We found that gaze was more stable for white-on-black than black-on-grey fixation targets. Gaze was also more stable (lower spatial spread, microsaccade, and drift displacement) for fixation targets with a small central feature but these targets also yielded higher microsaccade rates than larger fixation targets without such a small central feature. In conclusion, there is not a single best fixation target that minimizes all aspects of fixational eye movements. Instead, if one wishes to optimize for minimal spatial spread of the gaze position, microsaccade or drift displacements, we recommend using a target with a small central feature. If one instead wishes to optimize for the lowest microsaccade rate, we recommend using a larger target without a small central feature.
© 2025. The Author(s).
Keywords: Humans; Fixation, Ocular/physiology; Eye-Tracking Technology; Male; Female; Adult; Young Adult; Saccades/physiology; Eye Movements/physiology; Retina/physiology; Photic Stimulation